IMI2-PainCare-BioPain-RCT1: study protocol for a randomized, double-blind, placebo-controlled, crossover, multi-center trial in healthy subjects to investigate the effects of lacosamide, pregabalin, and tapentadol on biomarkers of pain processing observed by peripheral nerve excitability testing (NET): study protocol - Nochi, Zahra; Pia, Hossein; Bloms-Funke, Petra; Boesl, Irmgard; Caspani, Ombretta; Chapman, Sonya C.; Fardo, Francesca; Genser, Bernd; Götz, Marcus; Kostenko, Anna; Leone, Caterina; Li, Thomas; et al. (Trials, 2022)
Few new drugs have been developed for chronic pain. Drug development is challenged by uncertainty about whether the drug engages the human target sufficiently to have a meaningful pharmacodynamic effect. IMI2-PainCare-BioPain-RCT1 is one of four similarly designed studies that aim to link different functional biomarkers of drug effects on the nociceptive system that could serve to accelerate the future development of analgesics. This study focusses on biomarkers derived from nerve excitability testing (NET) using threshold tracking of the peripheral nervous system. This is a multisite single-dose, subject and assessor-blind, randomized, placebo-controlled, 4-period, 4-way crossover, pharmacodynamic (PD), and pharmacokinetic (PK) study in healthy subjects. Biomarkers derived from NET of large sensory and motor fibers and small sensory fibers using perception threshold tracking will be obtained before and three times after administration of three medications known to act on the nociceptive system (lacosamide, pregabalin, tapentadol) and placebo, given as a single oral dose with at least 1 week apart. Motor and sensory NET will be assessed on the right wrist in a non-sensitized normal condition while perception threshold tracking will be performed bilaterally on both non-sensitized and sensitized forearm skin. Cutaneous high-frequency electrical stimulation is used to induce hyperalgesia. Blood samples will be taken for pharmacokinetic purposes and pain ratings as well as predictive psychological traits will be collected. A sequentially rejective multiple testing approach will be used with overall alpha error of the primary analysis split across the two primary outcomes: strength-duration time constant (SDTC; a measure of passive membrane properties and nodal persistent Na+ conductance) of large sensory fibers and SDTC of large motor fibers comparing lacosamide and placebo. The key secondary endpoint is the SDTC measured in small sensory fibers. Remaining treatment arm effects on key NET outcomes and PK modelling are other prespecified secondary or exploratory analyses. Measurements of NET using threshold tracking protocols are sensitive to membrane potential at the site of stimulation. Sets of useful indices of axonal excitability collectively may provide insights into the mechanisms responsible for membrane polarization, ion channel function, and activity of ionic pumps during the process of impulse conduction. IMI2-PainCare-BioPain-RCT1 hypothesizes that NET can serve as biomarkers of target engagement of analgesic drugs in this compartment of the nociceptive system for future Phase 1 clinical trials. Phase 2 and 3 clinical trials could also benefit from these tools for patient stratification. This trial was registered 25/06/2019 in EudraCT ( 2019-000942-36 ).